Reforming EU car labels: How to achieve consumer-friendly transparency? - Nikolai Badenhoop; Max Riedel (Leibniz Institute for Financial Research SAFE, 2024)
We examine the EU car labelling regime for CO2 emissions and fuel efficiency under Directive 1999/94/EC and document strongly diverging national labelling methodologies. Our contribution is fourfold. First, we distil the most relevant economic and behavioural research findings on car labelling. Labels effectively help consumers make informed decisions if they are well-designed, comprehensible, and informative about hidden costs. Second, we compare the national car labelling methodologies and find stark inconsistencies, undermining the EU's effort to decarbonise the car sector. Empirically, we find heterogeneous distributions of the national labels if applied to the national and EU car fleets. Third, we assess the EU energy efficiency labelling regime for electric appliances under Regulation (EU) 2017/1369 as a labelling role model. Finally, we propose a standardised EU car label with comparative information in two distinct coloured scales using absolute labelling thresholds for CO2 emissions and fuel or energy efficiency.
Keywords: R4; K30; K32; L92; L98; Q48; Q58; 330; Car labels; CO2 emissions; Energy efficiency; Fuel economy; Directive 1999/94/EC; Passenger cars; Sustainable transport